Component leasing on the World Wide Web - Hans-Arno Jacobsen; G. Riessen; Oliver Günther (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
MMM is an infrastructure for managing the deployment and use of distributed application services on the WWW. MMM propagates a paradigm that enables the leasing of software components, as opposed to the classical software licensing model Applications reside and execute on the software provider's platforms, but are managed through the MMM infrastructure. Users interact with the application services through a standard Internet browser not requiring any additional software. The MMM user interface offers users a virtual file space, application service composition functions: execution support, and visualization features. The MMM implementation is based on standard Web technologies, such as HTML, XML, and MetaHTML, distributed object computing frameworks, such as CORBA, and database technology, such as ODBC. In this paper we give a technical account of the MMM architecture and discuss its primary features.
urn:nbn:de:kobv:11-10046329
Keywords: 330